2019
DOI: 10.3390/molecules24193580
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Inhibition Profiles of Coumarin-Based Compounds Against Human Carbonic Anhydrases: Synthesis, Biological, and In Silico Evaluation

Abstract: Carbonic anhydrases (CAs, EC 4.2.1.1) catalyze the fundamental reaction of CO2 hydration in all living organisms and are actively involved in the regulation of a plethora of pathological and physiological conditions. A set of new coumarin/ dihydrocoumarin derivatives was here synthesized, characterized, and tested as human CA inhibitors. Their inhibitory activity was evaluated against the cytosolic human isoforms hCA I and II and the transmembrane hCA IX and hCA XII. Two compounds showed potent inhibitory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The molecular docking studies are facilitated to understand the mechanism behind the selective potency and inhibition tendency of these three compounds against hCA II. Previously reported coumarin derivatives as hCA II inhibitors revealed the interaction of substituents with active site residues and non-involvement of the coumarin ring due to steric hindrance, thus exhibiting an innovative mechanistic approach where the coumarin ring could not enter deep into the active pocket of the enzyme due to bulkiness and rigidity, which therefore could not be hydrolyzed due to the esterase activity of CA II. The attachment of the molecule at the entrance of the cavity of the enzyme blocks and deshapes the active site, so the natural substrate could not enter into the enzyme pocket.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular docking studies are facilitated to understand the mechanism behind the selective potency and inhibition tendency of these three compounds against hCA II. Previously reported coumarin derivatives as hCA II inhibitors revealed the interaction of substituents with active site residues and non-involvement of the coumarin ring due to steric hindrance, thus exhibiting an innovative mechanistic approach where the coumarin ring could not enter deep into the active pocket of the enzyme due to bulkiness and rigidity, which therefore could not be hydrolyzed due to the esterase activity of CA II. The attachment of the molecule at the entrance of the cavity of the enzyme blocks and deshapes the active site, so the natural substrate could not enter into the enzyme pocket.…”
Section: Resultsmentioning
confidence: 99%
“… 52 , 53 Earlier studies from the literature revealed that some of the coumarin derivatives could not access the enzyme cavity of CA due to bulkiness, which therefore could not be hydrolyzed by the esterase activity of the enzyme. 54 57 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past four decades, great attention has been directed to the design and synthesis of coumarinbased prodrugs in an attempt to enhance the therapeutic efficacy of many drugs [14]. This type of prodrug is utilized for alcohol-and amine-containing compounds to improve their lipophilicity [15] and minimize their metabolic inactivation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Two compounds exhibited potent inhibitory activity against hCA IX, showing better or equal potency that acetazolamide used as a reference drug. For the study of the binding mode of this class coumarins/dihydrocoumarins within the active site of hCA IX and XII computational methods were used, validating hCA IX and XII as anti-tumor targets [19].…”
mentioning
confidence: 99%